Assessing Teachers’ Pedagogical Performance under the Merdeka Curriculum in Indonesian Vocational School - Ismiyati Ismiyati; Tusyanah Tusyanah; Mar'atus Sholikah; Teguh Hardi Raharjo; Sulistyawati Sulistyawati; Djoko Legowo (International Journal of Pedagogy and Teacher Education, 2026)
The implementation of the Merdeka Curriculum in Indonesia requires teachers to demonstrate strong pedagogical performance aligned with student-centered learning, flexible instructional design, and competency-based assessment. However, empirical evidence on variations in teachers’ pedagogical performance, particularly in vocational education, remains limited. This study aims to identify clusters of teachers’ pedagogical performance and to describe the characteristics of each cluster within the context of the Merdeka Curriculum. A quantitative approach was employed involving 99 vocational high school teachers from the Office Management and Business Services (OMBS) program in Central Java, Indonesia. Data were collected using a structured questionnaire covering lesson planning, instructional implementation, classroom management, and assessment practices. K-means cluster analysis was applied to classify teachers based on similarities in pedagogical performance. The findings reveal three distinct clusters of pedagogical performance: low (35%), moderate (38%), and high (27%). The high-performance cluster is characterized by systematic lesson planning, active learning strategies, and consistent use of formative assessment. The moderate cluster demonstrates relatively adequate instructional planning but limited innovation in instructional practice. The low-performance cluster reflects teacher-centered practices and restricted assessment variation. These findings highlight the heterogeneous nature of teachers’ pedagogical performance in implementing the Merdeka Curriculum. These findings suggest the need for targeted professional development, particularly for teachers in the moderate and low clusters, to support the adoption of more student-centered and competency-based practices